STRATEGI KOMUNIKASI BALI SHARKS DALAM MENGEDUKASI MASYARAKAT BALI UNTUK MENJAGA EKOSISTEM LAUT - Heryanti, Tannya Aeni; Pascarani, Ni Nyoman Dewi; Pradipta, Ade Devia (E-Jurnal Medium, 2017)
ABSTRACT Damage on marine ecosystem is one of the problems in Indonesia that impact to human life. The imbalance of the food chain in the oceans caused by excessive shark exploitation is one of the causes of damage to marine ecosystems. Another reason is the lack of public awareness caused by ignorance of the importance of maintaining marine ecosystems. The lack of government efforts to repair damage made Bali Sharks as a non-profit organization to help provide education and information to the people, especially the people in Bali. In this study, the author tries to find out Bali Sharks’ communication strategy in educating the people of Bali to maintain the marine ecosystem. This research is a descriptive qualitative research with data collection using participant observation, in-depth interview, and documentation study. Informants selected based on purposive sampling. Data analysis used Milles and Huberman interaction model. The results of this study show that Bali Sharks provides education to the people of Bali through new media, print media, electronic media, special events, and personal sales as channels in the communication strategy undertaken. The communication messages are based on the purpose and vision of Bali Sharks mission which generally consists of information and education about sharks and current marine ecosystem conditions, and solutions to improve marine ecosystems. The messages convey use different techniques and channels to see based by audience ‘s needed. Communicators are not only from Bali Sharks’ team but also the Bali Sharks’ audience who re-spread the information to other audiences. The communication strategy of Bali Sharks is expected to raise the awareness of the Balinese community on issues related to shark protection from over-exploitation, salvation of marine ecosystems, and more conservative in choosing seafood. Keywords: strategy communication, non-profit organization, damage on marine ecosystem, Bali Sharks, save sharks